2019
DOI: 10.1111/febs.15107
|View full text |Cite
|
Sign up to set email alerts
|

A guide to assessing endoplasmic reticulum homeostasis and stress in mammalian systems

Abstract: The endoplasmic reticulum (ER) is a multifunctional organelle that constitutes the entry into the secretory pathway. The ER contributes to the maintenance of cellular calcium homeostasis, lipid synthesis and productive secretory, and transmembrane protein folding. Physiological, chemical, and pathological factors that compromise ER homeostasis lead to endoplasmic reticulum stress (ER stress). To cope with this situation, cells activate an adaptive signaling pathway termed the unfolded protein response (UPR) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 136 publications
2
62
0
Order By: Relevance
“…Previous studies have demonstrated that endoplasmic reticulum (ER) stress serves an essential role in inflammation and cytokine production by macrophages (6,7). The activation of macrophages by lipopolysaccharides (LPS) leads to the unfolded protein response, which results in the activation of three ER stress markers on the ER membrane: Inositol-requiring enzyme 1α (IRE1α), PKR-like endoplasmic reticulum kinase (PERK) and activating transcription factor 6 (ATF6) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that endoplasmic reticulum (ER) stress serves an essential role in inflammation and cytokine production by macrophages (6,7). The activation of macrophages by lipopolysaccharides (LPS) leads to the unfolded protein response, which results in the activation of three ER stress markers on the ER membrane: Inositol-requiring enzyme 1α (IRE1α), PKR-like endoplasmic reticulum kinase (PERK) and activating transcription factor 6 (ATF6) (6).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting membranes were incubated with primary antibodies for 16 h at 4 °C, washed with PBS and incubated for 1 h with goat anti‐rabbit secondary antibodies at room temperature (Invitrogen) prior revelation using chemiluminescence. The antibodies used were as previously described [40].…”
Section: Methodsmentioning
confidence: 99%
“…Clarified lysates were complemented with 20 µl of 5 times reducing Laemmli sample buffer prior heat-denaturation and used in Western blot experiments with the indicated antibodies (at 1/1000 dilutions). For RNA preparation, cells were lyzed using 1ml of Trizol reagent per plate and RNA was extracted according to the manufacturer’s instructions (Thermo Fisher Scientific) and PCR analyses performed using previously described protocols [11].…”
Section: Methodsmentioning
confidence: 99%